2015
DOI: 10.1007/s12250-015-3676-2
|View full text |Cite
|
Sign up to set email alerts
|

RNA chaperones encoded by RNA viruses

Abstract: RNAs are functionally diverse macromolecules whose proper functions rely strictly upon their correct tertiary structures. However, because of their high structural flexibility, correct folding of RNAs is challenging and slow. Therefore, cells and viruses encode a variety of RNA remodeling proteins, including helicases and RNA chaperones. In RNA viruses, these proteins are believed to play pivotal roles in all the processes involving viral RNAs during the life cycle. RNA helicases have been studied extensively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 62 publications
(98 reference statements)
1
6
0
Order By: Relevance
“…9) and acting in an ATP-independent manner, which has been demonstrated for NS in strand displacement experiments (42). Second, the avian reovirus NS protein, which is functionally homologous to mammalian reovirus NS (64, 65), acts as an RNA chaperone in vitro (27), as does the rotavirus NSP2 nonstructural protein (28,63). Third, our cryo-EM analysis demonstrated that NS coats RNAs and forms filamentous structures (Fig.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…9) and acting in an ATP-independent manner, which has been demonstrated for NS in strand displacement experiments (42). Second, the avian reovirus NS protein, which is functionally homologous to mammalian reovirus NS (64, 65), acts as an RNA chaperone in vitro (27), as does the rotavirus NSP2 nonstructural protein (28,63). Third, our cryo-EM analysis demonstrated that NS coats RNAs and forms filamentous structures (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…These results suggest that NS binding to RNA leads to RNA rearrangements allowing the RNA to migrate through the gel matrix. RNA-remodeling proteins that resolve RNA structures are called RNA chaperones (62), which are encoded by some RNA viruses (63). There are three lines of evidence from our study and others suggesting that NS is an RNA chaperone.…”
Section: Discussionmentioning
confidence: 62%
“…An important group of RNA chaperones are viral nucleocapsid proteins, which facilitate many nucleic-acid-dependent processes in viral life cycles 1215 . Comparisons among these chaperones reveal very few structural similarities, but many of them are enriched in positively charged and polar residues, resulting in proteins that are known or predicted to be disordered 13,16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons among these chaperones reveal very few structural similarities, but many of them are enriched in positively charged and polar residues, resulting in proteins that are known or predicted to be disordered 13,16,17 . Their chaperone activity is present both in vitro and in vivo 3,5,8,12,13 , and the intrinsically disordered regions are both necessary and sufficient for this function 15 . These findings give rise to a question of fundamental importance: How do RNA chaperones function without a well-defined structure?…”
Section: Introductionmentioning
confidence: 99%
“…RNA chaperones are a heterogeneous group of proteins that can destabilize RNA duplexes and promote correct RNA folding in an ATP-independent fashion (20). A wide range of RNA viruses, including flavivirus (21), picornavirus (22), alphavirus (23), coronavirus (24), reovirus (25), iflavirus (26), and alphatetravirus (27), have been found to encode their own RNA helicases and/or RNA chaperones (28).…”
mentioning
confidence: 99%